Exploring the Driving Factors and Impact of Business Satisfaction and Social Media Marketing on Virtual Tourism Product Adoption: A Case Study of MSME Members in Indonesia - Agiv Alfan Khakim; Zunan Setiawan (www.amertainstitute.com, 2024)
Adoption of virtual tourism products is a transformational opportunity for Micro, Small and Medium Enterprises (MSMEs) to increase their competitiveness and market presence. This study, Exploring the Drivers and Impact of Business Satisfaction and Social Media Marketing on the Adoption of Virtual Tourism Products: A Case Study of MSME Members in Indonesia, analyzes the determinants of virtual tourism technology adoption by MSMEs. Using the UTAUT theoretical framework, this research evaluates effort expectancy (ease of use), performance expectancy (expected benefits), MSME satisfaction, and adoption intention. Results from 317 MSME respondents were analyzed using PLS-SEM 4.0. The study found that MSME satisfaction is a key factor in determining adoption intentions, influenced by information access, uncertainty reduction, and competitor analysis. Meanwhile, effort expectancy and performance expectancy do not directly predict intentions, but are important in forming initial perceptions. Social media marketing also acts as an additional driver that increases the visibility of virtual products. This research provides strategic insights for MSMEs to utilize immersive technology, highlighting the importance of user-friendly products and comprehensive support systems. With the increasing adoption of virtual technology in Indonesia's tourism sector, these findings provide a roadmap for MSMEs to utilize innovation effectively.